PENGARUH KEPERCAYAAN DAN MINAT BELI MASYARAKAT SECARA ONLINE - Rahmi; Syafitri (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
This research was conducted to determine the effect of people's trust and buying interest online. Trust is considered an important factor and is one of the critical factors in stimulating online transactions. When trust is higher, of course, it will be used as a measure to foster consumer buying interest to transact online, so the higher the trust, the higher the buying interest. Positive trust certainly affects consumer interest in shopping online because they believe that sellers are able to carry out their business activities properly and can be trusted by sending the purchased products to consumers.